Exome sequencing of 18,994 ethnically diverse patients with suspected rare Mendelian disorders - Heonjong Han; Go Hun Seo; Seong-In Hyun; Kisang Kwon; Seung Woo Ryu; Rin Khang; Eugene Lee; JiHye Kim; Yongjun Song; Won Chan Jeong; Joohyun Han; Dong-wook Kim; et al. (npj Genomic Medicine)
Abstract We investigated the effectiveness of exome sequencing (ES) in diagnosing ethnically diverse patients with rare genetic disorders. A total of 18,994 patients referred to a single reference laboratory for ES between 2020 and 2022 were studied for the diagnostic rate and factors influencing the diagnostic rate. The overall diagnostic rate was 31.8%. Dermatological disorders, skeletal disorders, and neurodevelopmental disorders disease categories, early age-of-onset, presence of consanguinity, and the presence of parental sequencing data were found to be correlated with a higher diagnostic rate. Nearly 68K variants were identified in our dataset at a higher frequency than that observed in gnomAD 4.0. Of these, 507 variants could be classified as likely benign, representing 0.04% of non-benign variants in ClinVar (507/1,433,904) and 0.20% of the non-benign ClinVar variants observed at least once in our cohort (507/276,777). The overall diagnostic rate is comparable to that observed in other large cohort studies with less diverse ethnic backgrounds.